Selection of artificial diets for Pseudaletia sequax Franclemont, 1951 (Lep.: Noctuidae) - Salvadori, José Roberto; Parra, José Roberto Postali (Pesquisa Agropecuaria Brasileira, 2014)
A study was conducted to select suitable artificial diets to rear larvae of Pseudaletia sequax Franc., 1951 (Lep., Noctuidae). The work was carried out in laboratory, under controlled temperature, air moisture and photophase conditions. From sixteen dieta three were selected, in relation to viability and length of larval and pupal periods and to pupal weight. These dieta were compared, with more details, considering biological parameters during three generations, food consumption and utilization index and cost of insect production. Two more suitable dieta were identified for this specie: one composed by beans, casein, soybean flour, wheat germ and yeast, and the other one composed by beans, wheat germ and yeast.